System Dynamics Model of Transit Oriented Development Implementation to Reduce Carbon Emission from Urban Transportation - Raulia Riski; Erma Suryani; Ulfa Emi Rahmawati; Gustin Ayu Cahyandini (Institut Teknologi Sepuluh Nopember, 2020)
The biggest carbon emissions in urban areas are generated from the transportation system, including in Surabaya City where the transportation sector contributes 5.48 million tons of carbon emissions per year, or about 96% of the total air emissions there. With the cities rapid development, urban transportation systems need to be managed appropriately to avoid environment damage. The most effective way to reduce carbon emissions from the transportation system is by reducing the number of private vehicles uses. TOD is one of the solutions that can be applied, which is through the integration of mixed land development and the construction of transit mode transportation systems. TOD allows people to carry out various daily activities with close transportation distances, either using transit modes, walking, or cycling. This study aims to show the benefits of applying TOD in reducing carbon emissions from the transportation sector in Surabaya using a system dynamics model. The model produced can be used as a reference or consideration for the government and other related parties in developing strategies and policies related to the implementation of TOD. Future studies can analyze several TOD scenarios that can be carried out to reduce carbon emissions from the transportation sector in Surabaya.